2020
DOI: 10.1155/2020/2315106
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Ameliorates Aβ Pathology by Insulin-Degrading Enzyme in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease. The accumulation of amyloid beta (Aβ) is the main pathology of AD. Metformin, a well-known antidiabetic drug, has been reported to have AD-protective effect. However, the mechanism is still unclear. In this study, we tried to figure out whether metformin could activate insulin-degrading enzyme (IDE) to ameliorate Aβ-induced pathology. Morris water maze and Y-maze results indicated that metformin could improve the learning and memory ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…In addition, HBOT elevated IDE and LRP1 levels, thus promoting Aβ degradation and clearance. These findings are in accordance with evidence showing that elevating either activity of the degradation pathway by enhancing IDE levels [ 76 , 77 ] or of clearance pathway by changing LRP1 levels [ 78 ] leads to a reduction in amyloid burden. Our finding that the number of microglia per plaque volume increased following HBOT suggests that microglia were recruited to plaques, possibly supporting plaque degradation [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HBOT elevated IDE and LRP1 levels, thus promoting Aβ degradation and clearance. These findings are in accordance with evidence showing that elevating either activity of the degradation pathway by enhancing IDE levels [ 76 , 77 ] or of clearance pathway by changing LRP1 levels [ 78 ] leads to a reduction in amyloid burden. Our finding that the number of microglia per plaque volume increased following HBOT suggests that microglia were recruited to plaques, possibly supporting plaque degradation [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is prescribed to the elderly population and has relatively safe profile even after chronic treatment [ 93 ]. Application of metformin has been shown beneficial in restoring energy homeostasis in the brain of APP/PS1 mice providing additional support for our findings [ 94 ]. A recent study conducted in a large Finish population of older people with diabetes demonstrated that long-term and high-dose metformin use do not increase incidences of AD and is associated with a lower risk of developing AD [ 95 ].…”
Section: Discussionsupporting
confidence: 80%
“…Metformin also restored spine density, surface AMPA subunit GluA1 trafficking, LTP expression and spatial memory in the APP/PS1 mouse by inhibiting cyclin-dependent kinase 5 hyper-activation and cyclin-dependent kinase 5-dependent tau hyperactivation( Wang et al, 2020 ). Furthermore, metformin could activate AMPK and insulin-degrading enzyme in the brain of APP/PS 1 mice, which might be the key neuroprotection mechanism of metformin( Lu et al, 2020 ). Metformin treatment for 8 weeks improved memory in the SAMP8 mouse model of sporadic AD, which was associated with the decreased levels of APPc99 and pTau404( Farr et al, 2019 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%